Control of nozzle flow in a suddenly expanded duct with micro jets - Baig, Maugal Ahmed Ali; Khan, Sher Afghan; Rathakrishnan, E. (ijesat.org, 2012)
This paper presents results of an experimental investigation carried out to control the base pressure in a suddenly expanded axi-symmetric passage. Four micro-jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region were employed as active controls. The tests were conducted for Mach numbers 1.25, 1.3, 1.48, 1.6, 1.8, 2.0, 2.5 and 3.0. The area ratio of the present study was 6.25. The length-to-diameter ratio of the enlarged duct was varied from 10 to 1. Nozzles generating the above jet Mach numbers were operated with nozzle pressure ratio (NPR) in the range 3 to 11. In addition to base pressure, the wall pressure distribution in the duct was also measured. It is found that the micro jets can serve as active controllers for base pressure. On the positive side the gain was 30 per cent whereas on the negative side the decrease in base pressure was 40 per cent. After scanning the wall pressure in the enlarged duct it is found that the wall pressure distribution is not adversely affected by the micro jets.